Antimicrobial, Anti-Inflammatory, Antiparasitic, and Cytotoxic Activities of Laennecia confusa - María G. Martínez Ruiz; Melissa Richard-Greenblatt; Zaida N. Juárez; Yossef Av-Gay; Horacio Bach; Luis R. Hernández (The Scientific World Journal)
The current paper investigated the potential benefit of the traditional Mexican medicinal plant Laennecia confusa (Cronquist) G. L. Nesom (Asteraceae). Fractions from the hexane, chloroform, methanol, and aqueous extracts were analyzed for antibacterial, antifungal, anti-inflammatory, and antiparasitic activities. The antimicrobial activity of the extracts and fractions was assessed on bacterial and fungal strains, in addition to the protozoa Leishmania donovani, using a microdilution assay. The propensity of the plant's compounds to produce adverse effects on human health was also evaluated using propidium iodine to identify damage to human macrophages. The anti-inflammatory activity of the extracts and fractions was investigated by measuring the secretion of interleukin-6. Chemical analyses demonstrated the presence of flavonoids, cyanogenic and cardiotonic glycosides, saponins, sesquiterpene lactones, and triterpenes in the chloroform extract. A number of extracts and fractions show antibacterial activity. Of particular interest is antibacterial activity against Staphylococcus aureus and its relative methicillin-resistant strain, MRSA. Hexanic and chloroformic fractions also exhibit antifungal activity and two extracts and the fraction CE 2 antiparasitic activity against Leishmania donovani. All bioactive extracts and fractions assayed were also found to be cytotoxic to macrophages. In addition, the hexane and methane extracts show anti-inflammatory activity by suppressing the secretion of interleukine-6.